2009
DOI: 10.1002/jbm.a.32498
|View full text |Cite
|
Sign up to set email alerts
|

Bone ingrowth into porous silicon nitride

Abstract: Achieving solid skeletal attachment is a requirement for the clinical success of orthopedic implants. Porous or roughened surfaces and coatings have been developed and used with mixed success to achieve attachment due to bone ingrowth. Silicon nitride is a high performance ceramic whose strength, imaging properties, and biocompatibility make it a candidate material for orthopedic implants. A porous form of silicon nitride, cancellous-structured ceramic (CSC), has been developed. CSC is a nonresorbable, partial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(32 citation statements)
references
References 67 publications
0
30
0
Order By: Relevance
“…For Si 3 N 4 , several studies demonstrated its osseointegration capabilities. Anderson et al showed osseous penetration of up to 3 mm in ∼72% porous Si 3 N 4 with excellent vascularization twelve weeks after implantation in an ovine model [105]. Similar studies by Guedes e Silva et al showed good boney apposition for Si 3 N 4 samples in rabbits evaluated eight weeks after implantation [103,104].…”
Section: Osseointegrationmentioning
confidence: 77%
See 2 more Smart Citations
“…For Si 3 N 4 , several studies demonstrated its osseointegration capabilities. Anderson et al showed osseous penetration of up to 3 mm in ∼72% porous Si 3 N 4 with excellent vascularization twelve weeks after implantation in an ovine model [105]. Similar studies by Guedes e Silva et al showed good boney apposition for Si 3 N 4 samples in rabbits evaluated eight weeks after implantation [103,104].…”
Section: Osseointegrationmentioning
confidence: 77%
“…Si 3 N 4 has been shown to be biocompatible, possessing favorable cell interaction characteristics [83,84,[97][98][99][100][101][102]. These and other studies indicate that porous or unpolished Si 3 N 4 osteointegrates with adjacent bone [102][103][104][105][106] and exhibits bacteriostasis [106,107] . In its dense and polished form, it has been shown to produce implants with exceptionally low wear rates [108][109][110][111][112][113][114][115][116][117][118].…”
Section: Silicon Nitridementioning
confidence: 97%
See 1 more Smart Citation
“…[56][57][58][59] A cancellous-structured porous silicon nitride composite ceramic has been developed and is in commercial use as a spinal fusion implant; cylindrical implants have shown bone ingrowth rates similar to those reported for porous titanium, indicating that porous silicon nitride is an excellent substrate for implants designed for direct, biological skeletal fixation. 60 New bone forms even in the cortical region of the rabbit tibia, and around silicon nitride implants, suggesting that the material is osteoconductive, and promotes stable osseous fixation. 61 …”
Section: Orthopaedic Applications Of Silicon Nitridementioning
confidence: 99%
“…Porous silicon (pSi) shows potential as a biocompatible scaffold for applications in orthopaedics (Li et al, 1998;Coffer et al, 2005;Whitehead et al, 2008;Anderson et al, 2010), oncology (Zhang et al, 2005;Mann et al, 2011;Park et al, 2011) and ophthalmology (Low et al, 2006;Cheng et al, 2008;Low et al, 2009;Kashanian et al, 2010). For use in ophthalmic implants designed to deliver drugs or cells to the eye, the advantages of pSi include its large surface area for drug-loading and cell attachment, and good ocular biocompatibility (Low et al, 2009;Kashanian et al, 2010).…”
Section: Introductionmentioning
confidence: 99%